Impact of Environmental Factors on the Prevalence Changes of Allergic Diseases in Elementary School Students in Ulsan, Korea: A Longitudinal Study - Lee, Jiho (Int J Environ Res Public Health, 2020)
We examined the effect of long-term changes in environmental factors on the prevalence of allergic diseases in elementary school students in Ulsan, Korea. This longitudinal study was conducted among 390 students who were enrolled from three elementary schools in Ulsan in both the first (2009–2010) and second survey (2013–2014). The International Study of Asthma and Allergies in Childhood questionnaire was used to determine the prevalence of allergic diseases and hazardous environmental factors. Generalized estimating equations (GEE) were used to investigate the impact of environmental factors on the change in the prevalence of allergic diseases. The survey revealed that an increased risk of allergic rhinitis was associated with exposure to secondhand smoke, the remodeling of a room, the replacement of wallpaper or flooring, the use of a humidifier, and irritation symptoms of air pollution. Atopic dermatitis was associated with the relocation to or repairs of a new house, and allergic conjunctivitis was associated with low levels of weekly physical activity, the use of insecticides, and irritation symptoms of air pollution. The results indicate that (1) allergic rhinitis and atopic dermatitis are associated with indoor pollution, (2) allergic conjunctivitis is associated with exposure to indoor chemical compounds and low levels of weekly physical activity. This study suggested that the proper evaluation and decrease in the number of environmental risk factors could effectively manage allergic diseases.